Are poor responders patients at higher risk for producing aneuploid embryos in vitro? - Setti, Amanda Souza; de Almeida Ferreira Braga, Daniela Paes; Savio Figueira, Rita de Cassia; Azevedo, Matheus de Castro; Iaconelli, Assumpto; Borges, Edson [UNESP] (Springer/plenum Publishers, 2011)
Purpose To test the hypothesis that aged women with poor ovarian response express an increase on embryo chromosomal alterations when compared to aged women who presented normal response.Methods Couples undergoing intracytoplasmic sperm injection cycles with preimplantation genetic screening, were subdivided into two groups: Poor Responder group (n = 34), patients who produced a parts per thousand currency sign4 oocytes; and Normoresponder group (n = 50), patients who produced a parts per thousand yen5 oocytes. Groups were compared regarding cycles' outcomes and aneuploidy frequency.Results There were no significant differences between and groups regarding the fertilization rate (p = 0.6861), clinical pregnancy (p = 0.9208), implantation (p = 0.6863), miscarriage (p = 0.6788) and the percentage of aneuploid embryos (p = 0.270). Embryo transfer rate was significantly lower on poor responder group (p = 0.0128) and logistic regression confirmed the influence of poor response on the chance of embryo transfer (p = 0.016).Conclusions Aged females responding poorly to gonadotrophins are not at a higher risk for producing aneuploid embryos in vitro.
Keywords: Intracytoplasmic sperm injection; Ovarian stimulation; Poor ovarian response; Preimplantation genetic screening